Global Cross-Talk of Genes of the Mosquito Aedes aegypti in Response to Dengue Virus Infection - Susanta K. Behura; Consuelo Gomez-Machorro; Brent W. Harker; Becky deBruyn; Diane D. Lovin; Ryan R. Hemme; Akio Mori; Jeanne Romero-Severson; David W. Severson (2011)
Background The mosquito Aedes aegypti is the primary vector of dengue virus (DENV) infection in humans, and DENV is the most important arbovirus across most of the subtropics and tropics worldwide. The early time periods after infection with DENV define critical cellular processes that determine ultimate success or failure of the virus to establish infection in the mosquito. Methods and Results To identify genes involved in these processes, we performed genome-wide transcriptome profiling between susceptible and refractory A. aegypti strains at two critical early periods after challenging them with DENV. Genes that responded coordinately to DENV infection in the susceptible strain were largely clustered in one specific expression module, whereas in the refractory strain they were distributed in four distinct modules. The susceptible response module in the global transcriptional network showed significant biased representation with genes related to energy metabolism and DNA replication, whereas the refractory response modules showed biased representation across different metabolism pathway genes including cytochrome P450 and DDT [1,1,1-Trichloro-2,2-bis(4-chlorophenyl) ethane] degradation genes, and genes associated with cell growth and death. A common core set of coordinately expressed genes was observed in both the susceptible and refractory mosquitoes and included genes related to the Wnt (Wnt: wingless [wg] and integration 1 [int1] pathway), MAPK (Mitogen-activated protein kinase), mTOR (mammalian target of rapamycin) and JAK-STAT (Janus Kinase - Signal Transducer and Activator of Transcription) pathways. Conclusions Our data revealed extensive transcriptional networks of mosquito genes that are expressed in modular manners in response to DENV infection, and indicated that successfully defending against viral infection requires more elaborate gene networks than hosting the virus. These likely play important roles in the global-cross talk among the mosquito host factors during the critical early DENV infection periods that trigger the appropriate host action in susceptible vs. refractory mosquitoes.